Analisis Kesesuaian Perairan Pesisir untuk Budidaya Rumput Laut Kappaphycus alvarezii Berdasarkan Parameter Fisika dan Kimia di Desa Tanah Kuning, Kalimantan Utara - Ery Gusman; Awaludin; Muhammad Firdaus; Ardiansyah (Samakia : Jurnal Ilmu Perikanan, 2026)
This study aims to analyze the suitability of coastal waters in Tanah Kuning Village, Bulungan Regency, for Kappaphycus alvarezii seaweed cultivation amidst the industrialization dynamics of the Indonesian Green Industrial Estate (KIHI). An exploratory descriptive method was employed, with four observation stations selected through purposive sampling. The analyzed parameters included physical aspects (current speed, depth, temperature, transparency) and chemical properties (salinity, pH, dissolved oxygen, nitrate, phosphate). Suitability levels were determined using a weighted scoring method. The results indicated that the water quality conditions in Tanah Kuning Village exhibit varying suitability levels across parameters, ranging from highly suitable (S1) to unsuitable (N). Accumulatively, the total suitability score was 58, classifying the area into the Suitable (S2) category. The primary limiting factors identified were the relatively deep waters (10–19 m) and strong current speeds (0.41–0.53 cm/s). To optimize this potential, innovation in cultivation technology, such as the use of more robust long-line methods and precise micro-siting in sheltered areas, is required to mitigate the risk of physical damage to the seaweed thallus.